2015
DOI: 10.1002/ddr.21270
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐Based Therapeutic Strategies for Targeting Mutant and Wild Type RAS in Cancer

Abstract: MicroRNAs (miRs) have been causally implicated in the progression and development of a wide variety of cancers. miRs modulate the activity of key cell signaling networks by regulating the translation of pathway component proteins. Thus, the pharmacological targeting of miRs that regulate cancer cell signaling networks, either by promoting (using miR-supplementation) or by suppressing (using anti-sense oligonucleotide based strategies) miR activity is an area of intense research. The RAS-Extracellular signal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 190 publications
(296 reference statements)
0
8
0
Order By: Relevance
“…Wild-type Ras is capable of promoting development of cancers 30 , including breast cancer 31 , and basal breast cancer in particular 21 32 . There is a large body of data supporting the concept that wild-type Ras plays a critical role in cells that harbor Ras mutations 33 . Using TCGA data, it has been reported that over 30% of basal-like breast cancers display KRAS gene amplifications 34 , and an increase in genomic DNA copy numbers at the KRAS2 locus was reported in 9 of 16 human basal-like tumors 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type Ras is capable of promoting development of cancers 30 , including breast cancer 31 , and basal breast cancer in particular 21 32 . There is a large body of data supporting the concept that wild-type Ras plays a critical role in cells that harbor Ras mutations 33 . Using TCGA data, it has been reported that over 30% of basal-like breast cancers display KRAS gene amplifications 34 , and an increase in genomic DNA copy numbers at the KRAS2 locus was reported in 9 of 16 human basal-like tumors 35 .…”
Section: Resultsmentioning
confidence: 99%
“…In 2005, MIRLET7 became the first tumor suppressive miRNA reported to downregulate RAS expression in lung tumors 27 . Later, numerous other miRNA were discovered to target RAS or its effector molecules in numerous cancers 28 . There are several miRNA reported to target KRAS other than MIRLET7 29 .…”
Section: The Association Of Ras Signaling Network With Cancer and MImentioning
confidence: 99%
“…Furthermore, these agents may alter physiological processes or may break the organ system function due to the accumulation, clearance, and excretion of these molecules. Hence, to it is necessary to take these therapeutic barriers into consideration so as to utilize miRNA-based therapeutics successfully 65 . Although making miRNA replacement therapy routine is not an easy task, it should be noted that miRNAs were found in mammals just a decade ago.…”
Section: Prospects Of Mir-483 In Dtcsmentioning
confidence: 99%